CENP-A Regulation and Cancer - Renaud-Pageot, Charlène; Quivy, Jean-Pierre; Lochhead, Marina; Almouzni, Geneviève (Frontiers in Cell and Developmental Biology, 2022)
In mammals, CENP-A, a histone H3 variant found in the centromeric chromatin, is critical for faithful chromosome segregation and genome integrity maintenance through cell divisions. Specifically, it has dual functions, enabling to define epigenetically the centromere position and providing the foundation for building up the kinetochore. Regulation of its dynamics of synthesis and deposition ensures to propagate proper centromeres on each chromosome across mitosis and meiosis. However, CENP-A overexpression is a feature identified in many cancers. Importantly, high levels of CENP-A lead to its mislocalization outside the centromere. Recent studies in mammals have begun to uncover how CENP-A overexpression can affect genome integrity, reprogram cell fate and impact 3D nuclear organization in cancer. Here, we summarize the mechanisms that orchestrate CENP-A regulation. Then we review how, beyond its centromeric function, CENP-A overexpression is linked to cancer state in mammalian cells, with a focus on the perturbations that ensue at the level of chromatin organization. Finally, we review the clinical interest for CENP-A in cancer treatment.